Complex Interplay Between Educational Leaders’ Leadership Styles And School Performance - Shapaka, Rehabeam (Papanda Publishier, 2026)
Using qualitative multiple case study research design that emanates from constructivist worldview, this study explores the complex interplay between educational leaders’ leadership styles and school performance. Data collected through the interview schedule and field notes. Criterion purposeful sampling technique used to select 20 educational leaders from 20 schools. Data analysis conducted using thematic analysis, typological analysis; content analysis using Atlas.ti. The study found that transformational leadership fosters environment which encourages collaboration, innovation, shared responsibility, empower staff, support sense of community leading to positive school performance. Instructional leadership play very important roles in focusing on teaching and learning. Distributed leadership focuses on collaborative discussions, redefining a compelling vision and guide decision-making process. Educational leaders should study and learn application of these leadership styles, apply them to optimise their success and/or enhance school performance. Educational leaders should integrate elements of these leadership styles to support school performance, enhance job satisfaction and promote school success. These leadership styles enhance and promote schools performance.